2007
DOI: 10.1016/j.drugalcdep.2006.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Retail marijuana purchases in designer and commercial markets in New York City: Sales units, weights, and prices per gram

Abstract: This paper documents the bifurcation of the market for commercial marijuana from the market for designer marijuana in New York City. Commercial marijuana is usually grown outdoors, imported to NYC, and of average quality. By contrast, several varities of designer marijuana are usually grown indoors from specially bred strains and carefully handled for maximum quality. The mechanisms for marijuana sales include street/park sellers, delivery services, private sales, and storefronts. Retail sales units vary from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 17 publications
0
44
0
Order By: Relevance
“…This market characteristic changed, at least temporarily, with the explosion of crack cocaine in the 1980s and 1990s when the social hierarchy of drug dealing changed primarily to vertically integrated dealing organizations comprised primarily of minorities (Johnson et al, 1990). The New York drug market continues to change as documented by recent research identifying a bifurcation of the market into commercial and designer marijuana sectors (Sifaneck, Ream, Johnson, & Dunlap, 2007). These sectors involve differences in ethnic composition, geographic location in the city, and quality of the drug.…”
Section: The Invitational Edge In Drug Marketsmentioning
confidence: 97%
“…This market characteristic changed, at least temporarily, with the explosion of crack cocaine in the 1980s and 1990s when the social hierarchy of drug dealing changed primarily to vertically integrated dealing organizations comprised primarily of minorities (Johnson et al, 1990). The New York drug market continues to change as documented by recent research identifying a bifurcation of the market into commercial and designer marijuana sectors (Sifaneck, Ream, Johnson, & Dunlap, 2007). These sectors involve differences in ethnic composition, geographic location in the city, and quality of the drug.…”
Section: The Invitational Edge In Drug Marketsmentioning
confidence: 97%
“…In most studies on pricing mechanisms in drug markets or, more specifically, in local cannabis markets [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], analysis of pricing mechanisms is based on quantitative and qualitative data used or produced by the police and/or judicial authorities. However, the latter are often biased because: (i) police investigation methods can be based on stereotypes (certain types of suspects could be neglected since they do not match known types of suspects, whereby the former may use other pricing mechanisms than the stereotype suspects [18,[30][31][32][33][34]; (ii) changing priorities in public drug policies and in investigation by police result in unsystematically collected data [19,24,34]; (iii) information on drug prices in police data is mostly limited to the amount of drugs seized whereas the value of these drugs is always derived from interrogations of the arrested person [16] who often undervalues his crop to avoid higher sentences; (iv) police rarely takes the phenomenon of quantity discounting into account (i.e.…”
Section: Price Setting In the Belgian Cannabis Distribution Chainmentioning
confidence: 99%
“…If, for example, dealers on average sold 0.9 g as 1 g, then multiplying the estimated grams per joint by 0.9 would recover the actual grams per joint. Sifaneck et al (2007) studied 99 retail marijuana transactions in Manhattan in 2005 and found that actual weights ranged from 11% higher to 24% lower than the advertised weight and that 75% of the transactions were less than 90% of the advertised weight. We do not have any more comprehensive data than this on the likely weight of "a gram" of marijuana.…”
Section: Resultsmentioning
confidence: 98%